The Changes Of Characteristic Fermented Milk During Room Temperature Storage - Sukmaningrum, Hidayanti; Trisna Darmayanti, Luh Putu; Diah Puspawati, Gusti Ayu Kadek (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2021)
Fermented milk is a functional food has beneficial to human health. The recommended concentration of probiotic bacteria to provide health benefits is 10 6 -10 8 CFU/ml of product. The storage temperature is one of the factor that affected the characteristics of fermented milk. This research was conducted to determine the effect of storage time at room temperature to the characteristics of fermented milk product and determine the length of maximum storage at room temperature. The research design was Completely Randomized Design with storage time treatment at room temperature for 0, 2, 4, 6, 8, 10, 12, and 14 days. Each treatment was repeated 2 times so that 16 experimental units were obtainned. The variables that were observed included total LAB, total acid, pH, and sensory evaluation (aroma, taste, and overall acceptance). Data were analyzed with analysis of variance, if the treatment had an effect on the variables then followed by Duncan multiple range Test. The results showed that the treatment of fermented milk in room temperature storage significantly affected the total acid, pH, total LAB, and sensory evaluation (aroma, taste, and overall acceptance). The maximum storage of the room temperature was days with total acid of 0.5%, pH 3.63, total LAB 7.71 log cfu/ml or 5.12 x 10 7 cfu/ml, the sensory of aroma, taste, and overall acceptance was liked.